Используя замену переменных, решите систему .
ху+х-у=7
х^2у - ху^2 =6

1

Ответы и объяснения

2013-10-28T16:06:14+04:00
( ху+х-у=7                                         ( xy=6                                ( xy=1
( х^y-xy^=6                                         ( x-y=1                               ( x-y=6
( xy+(x-y)=7                                       x=y+1                                  x=y+6
( xy(x-y)=6                                         (y+1)y=6                           (y+6)y=1
xy=m,  x-y=n                                       y^+y-6=0                          y^+6y-1=0     
 ( m+n=7                                              D=1-4*(-6)=25              D=36-4(-1)=40                  ( mn=6                                                 y1=-1-5 /2=-3             y1=-6-кор40/2=
m=7-n                                                 y2=-1+5/2=2                   =-6-2кор10/2=-3-кор10
(7-n)n=6                                             x1=-3+1=-2                    у2=-6+кор40/2=
7n-n^=6  |*(-1)                                     x2=2+1=3                  =-6+2кор10/2=-3+кор10 
n^-7n+6=0                                                                             х1=-3-кор10+6=3-кор10
n1=6, n2=1(теорема Виета)                                                х2=-3+кор10+6=3+кор10
  m1=7-6=1,  m2=7-1=6          
                                          Ответ:(-2;-3),(3;2),(3-кор10;-3-кор10),(3+кор10;-3+кор10)